A genetic linkage study of facioscapulohumeral (Landouzy-Déjérine) disease with 24 polymorphic DNA probes. - Upadhyaya, M (1989)
From analysis of DNA polymorphisms in a panel of 455 subjects from 25 families with facioscapulohumeral (Landouzy-Déjérine) disease, we have found no evidence for close linkage of the disease at 24 different genetic loci, including one from a candidate chromosomal region. Added to previous data, our results provide direction for future collaborative linkage studies.